Fournier's disease and anaerobic paraproctitis – different clinical forms of same pathological process? - M. A. Yegorkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To carry out analysis of literature data on necessity of the uniform approach to diagnostics and treatment of patients with Fournier’s disease (FD) and anaerobic paraproctitis (AP).Original positions. High mortality and morbidity at these diseases is caused by rapid generalization of process, development of septic states and multiorgan failure. A basis of treatment is the urgent surgical intervention in combination to application of antibacterial and detoxication agents. Modern principles of antibiotic selection and carryings out of surgical interventions, application of additional methods of treatment in postoperative period are analyzed. At FD and AP radical elimination of suppurative focus in optimal terms (3–6 days after disease onset), subsequent complex antibacterial and detoxication therapy result in regression of signs of inflammation and convalescence of the majority of patients.Conclusion. It is proposed to apply the «Fournier’s disease» term only to infection originating from genitalia, differentiating that from anaerobic paraproctitis, because extensive use of this term complicates analysis of prevalence.